PENERAPAN PRINSIP-PRINSIP PELAYANAN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN TERINTEGRASI DI PUSKESMAS LOMPOE KECAMATAN BACUKIKI KOTA PAREPARE - Sapri Sapri; Muhammad Amin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
The main study in this research is the Implementation of Service of Social Security Organizing Body (BPJS) Integrated Health at Lompoe Health Center, Bacukiki Sub-district, ParePare City. The population was taken from all BPJS participants in the puskesmas area with a population of 10,000 people, and a sample of 100 people using the slovin formula. Technique of collecting datanyamelalui observation, kuisioner, dokumentasi.Teknik Analysis of data that is descriptive quantitative. The results of the research indicate that the implementation of service principles of the Integrated Health Insurance Board (BPJS) in Lompoe Health Center of Bacukiki Sub-District of ParePare City is viewed from the ten indicators of service principle: simplicity, clarity, certainty of time, accuracy, security, responsibility, completeness of facilities and infrastructure, , discipline and comfort, obtained a good percentage of the results and memuskan. And obtained an ideal result of 77% of 100% expected results, this indicates that the principle of service is well implemented in Lompoe Community Health Center. Participant satisfaction on the service Social Security Administering Agency (BPJS) Integrated Health at Lompoe Community Health Center Bacukiki District ParePare City seen from the fifth indicators of satisfaction ie patient welfare, patient comfort, patient room condition, patient medical records and care unit obtained a good or satisfactory percentage. And obtained an ideal result of 78% of 100% expected results, this indicates that participants BPJS Health at Lompoe Community Health Center has been satisfied to receive services.